Desain dan Pengembangan Aplikasi Android Pemanggilan Ambulans Berdasarkan Jarak Terdekat Pasien - Rosyid R. Al Hakim; Hendra Purnawan; Rofingi Aji; Slamet Riyadi; Aditia P. Hamid; Miftakhul H. Sidiq; Agung Pangestu; Ariep Jaenul; Yanuar Z. Arief (Politeknik Negeri Bandung, 2021)
Desain dan Pengembangan Aplikasi Android Pemanggilan Ambulans Berdasarkan Jarak Terdekat Pasien